MC-1. A "designer" surfactant engineered for peptide synthesis in water at room temperature. Issue 10 (8th May 2019) - Cortes-Clerget, Margery; Spink, Summer E.; Gallagher, Gregory P.; Chaisemartin, Laurent; Filaire, Edith; Berthon, Jean-Yves; Lipshutz, Bruce H.
Abstract : A novel, solvent-inspired surfactant has been developed, where the core of its derived micelles is designed to accommodate peptide synthesis. Abstract : Aqueous micellar catalysis has previously been shown to be an enabling technology for green peptide synthesis. Nonetheless, in response to limitations associated with use of selected amino acids in peptide constructions, a new surfactant has been designed, inspired by the commonplace use of the environmentally egregious dipolar aprotic solvent DMSO. A new amphiphile, MC-1, introduces a highly polar sulfone component into the otherwise nonpolar region of a surfactant, and thus, into the inner cores of its derived nanomicelles. This has led not only to a solution to solubility issues, but also to high yields, ease of handling of reaction mixtures, and elimination of co-solvents. Gram scale reactions are also described herein.